2015
DOI: 10.1109/jsen.2014.2377775
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Spectrum Analysis-Based Scheme for Multiple Power Quality Disturbance Sensing Device

Abstract: This paper presents a methodology of cross-wavelet transform aided Fischer linear discriminant analysis (FLDA)-based feature selection and classification for sensing simultaneous occurrence of multiple power quality disturbances. A linear support vector machine is used for classification of the extracted features as it suits well with FLDA. This scheme is implemented in a general purpose microcontroller as a standalone module and the performance of the standalone module for sensing simultaneous occurrence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The MPDs, which are contaminated with Gaussian white noise, consist of the most popular SPDs in [2,5,7,8,10,11,17,19] in recent years. These studied SPDs include sag, swell, interruption, harmonic, flicker, oscillation, impulse and notch.…”
Section: Simulation Testmentioning
confidence: 99%
See 3 more Smart Citations
“…The MPDs, which are contaminated with Gaussian white noise, consist of the most popular SPDs in [2,5,7,8,10,11,17,19] in recent years. These studied SPDs include sag, swell, interruption, harmonic, flicker, oscillation, impulse and notch.…”
Section: Simulation Testmentioning
confidence: 99%
“…These studied SPDs include sag, swell, interruption, harmonic, flicker, oscillation, impulse and notch. The PDs are the sample rate of all test signals of ten cycles, which is 6.4 KHz, and the models of those SPDs are based on the IEEE PQ standard [27] and previous works [10,17] as shown in Table 2. Table 2.…”
Section: Simulation Testmentioning
confidence: 99%
See 2 more Smart Citations
“…An algorithm, based on Stockwell's transform, artificial neural network-based classifier and rule-based decision tree, is proposed. Some of the latest research on combined disturbance recognition can be found in [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%